Design and properties of novel gallium-doped injectable apatitic cements. (15th September 2015) - Mellier, Charlotte; Fayon, Franck; Boukhechba, Florian; Verron, Elise; LeFerrec, Myriam; Montavon, Gilles; Lesoeur, Julie; Schnitzler, Verena; Massiot, Dominique; Janvier, Pascal; Gauthier, Olivier; Bouler, Jean-Michel; et al.
Graphical abstract: Abstract: Different possible options were investigated to combine an apatitic calcium phosphate cement with gallium ions, known as bone resorption inhibitors. Gallium can be either chemisorbed onto calcium-deficient apatite or inserted in the structure of β-tricalcium phosphate, and addition of these gallium-doped components into the cement formulation did not significantly affect the main properties of the biomaterial, in terms of injectability and setting time. Under in vitro conditions, the amount of gallium released from the resulting cement pellets was found to be low, but increased in the presence of osteoclastic cells. When implanted in rabbit bone critical defects, a remodeling process of the gallium-doped implant started and an excellent bone interface was observed. Statement of Significance: The integration of drugs and materials is a growing force in the medical industry. The incorporation of pharmaceutical products not only promises to expand the therapeutic scope of biomaterials technology but to design a new generation of true combination products whose therapeutic value stem equally from both the structural attributes of the material and the intrinsic therapy of the drug. In this context, for the first time an injectable calcium phosphate cement containing gallium was designed with properties suitable for practical application as a local delivery system, implantable by minimally invasive surgery. This important and original paper reports the design and in-depth chemical and physical characterization of this groundbreaking technology.